2016
DOI: 10.1039/c6cp02160c
|View full text |Cite
|
Sign up to set email alerts
|

Role of ion-pair states in the predissociation dynamics of Rydberg states of molecular iodine

Abstract: Using femtosecond pump-probe ion imaging spectroscopy, we establish the key role of I(+) + I(-) ion-pair (IP) states in the predissociation dynamics of molecular iodine I2 excited to Rydberg states. Two-photon excitation of Rydberg states lying above the lowest IP state dissociation threshold (1st tier) is found to be followed by direct parallel transitions into IP states of the 1st tier asymptotically correlating to a pair of I ions in their lowest states I(+)((3)P2) + I(-)((1)S0), of the 2nd tier correlating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 24 publications
(51 reference statements)
4
19
0
Order By: Relevance
“…It has been well established that many such Rydberg states act as “doorways” to ion-pair states, ,,,,, which, assuming the dissociation of the ion-pair state is exceeded, can produce I + + I – photofragment pairs. Baklanov and co-workers have recently conducted nanosecond and femtosecond velocity-map imaging studies on the photofragmentation dynamics of 6d Rydberg states of I 2 . These experiments identified a number of dissociation channels mediated by ion-pair states, either directly to ion pair products or to electronically excited atoms through lower-lying Rydberg states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been well established that many such Rydberg states act as “doorways” to ion-pair states, ,,,,, which, assuming the dissociation of the ion-pair state is exceeded, can produce I + + I – photofragment pairs. Baklanov and co-workers have recently conducted nanosecond and femtosecond velocity-map imaging studies on the photofragmentation dynamics of 6d Rydberg states of I 2 . These experiments identified a number of dissociation channels mediated by ion-pair states, either directly to ion pair products or to electronically excited atoms through lower-lying Rydberg states.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work studying the dissociation dynamics of I 2 6d Rydberg states populated by two-photon absorption in the ultraviolet have identified several such predissociation pathways with picosecond lifetimes. 36 , 38 This study reported I – /I + ion-pair dissociation products with ∼0.25 eV KER and an approximately isotropic angular distribution, in qualitative agreement with the higher KER feature observed in Figure 8 , parts c and d. The significant broadness of this feature in the current data, in addition to the additional channels at much lower KER suggest the existence of multiple ion-pair dissociations, consistent with the observation of several Rydberg states of higher energy than the 6d the photoelectron spectra ( Figure 7 c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have not observed a direct dissociation process in the valence states following one-photon absorption, but dissociative fragments in the one-photon energy region have been observed upon Rydberg state excitation of the iodine molecule. A similar excitation/predissociation scheme may apply for the Rydberg state of Br 2 . , …”
Section: Resultsmentioning
confidence: 99%
“…Further, it is evident from the excitation energies of I emitting states illustrated in figure 6, and shown in table 1, that the excited I species derive from I 2 Rydberg states, where the '6p' levels correlate generally to states below the I 2 ionization limit and the other I emitters to Rydberg states that converge on excited I 2 + levels. An excitation scheme that conforms to these limitations is sketched in figure 8, and was suggested in recent pump-probe experiments examining predissociation of I 2 Rydberg states [55]. In that work photo-excitation to a single, higher I 2 Rydberg level led to dissociation on several lower Rydberg asymptotes via crossings of both former and latter Rydberg curves by the same high-lying ion-pair potential.…”
Section: The Imentioning
confidence: 93%